Annual review of comparative and international education 2015 - Wiseman, Alexander W., 1968-; Anderson, Emily (International perspectives on education and society ;, 2016)
The goal of the ARCIE volume is to examine current perspectives and future directions for the field using several essays as a context for discussion and analysis. The format of ARCIE pieces entails an analytic overview of published work in the field, noting key issues and future directions. It provides an important and well-cited international forum for the discussion of matters of comparative and international education theory, policy and practice.